Individual investment bankers’ reputation concerns and bond yield spreads: Evidence from China - Lyu, Huaili; Wang, Wenming; Xu, Si; Zhou, Jingting (Journal of Banking & Finance, 2022)
Using a sample of domestic corporate bonds issued by Chinese firms, this study examines the relationship between the reputation concerns of individual investment bankers and bond yield spreads. China provides an unbiased method to capture individual investment bankers’ reputation concerns in terms of the initial public offering qualification. We find a robust negative relationship between bond offering yields and the reputation concerns of individual investment bankers who underwrite the bonds, indicating that reputation concerns motivate individual investment bankers to provide high-quality underwriting services and in turn enhance the market valuation of bonds. This relationship is more pronounced for bond issues that have higher default risk and greater information asymmetry, underwritten by less reputable investment banks and rated by less reputable credit rating agencies, and issued by firms located in regions with weaker institutional environments. This study sheds new light on the importance of individual investment bankers’ attributes, particularly reputation capital, in determining the quality of bond underwriting services.